La Universitat de Cervera: Un projecte reformista frustrat. - PRATS, JOAQUIM (Scripta, 2020)
The University of Cervera, founded by Philip V, was an important milestone for Catalonia: on the one hand, it was born as a Bourbon project for the future and, on the other, it meant that historic Catalan universities had been abolished, under the policy repressive of the new monarch. This article discusses that institution and the failure of that project. The creation of the University must be situated in a reformist context of a centralist nature, typical of the new European monarchies that took as their image the court and action in domestic politics of Louis XIV. However, over the years, that proposal was thwarted.